Woman and the Body in Modern Japanese Poetry - Toshiko Ellis (Universitat de Barcelona, 2011)
The article focuses on the three contemporary Japanese poets Yosano Akiko, Sagawa Chika and Ito Hiromi as examples of women who break away from the conventions of “women’s poetry” and subvert the image of femininity which has been traditionally portrayed in poems written by Japanese women, at the same time that they preserve in their works themes related to the female sex. Taking as connecting point the female body and the way it is positioned in relation to the outside world, the article analyzes how Yosano, Sagawa and Ito -each in her own subversive way– use different languages to explore the female body itself, as well as themes such as female sexuality, love, motherhood and death.